Outcome of COVID‐19 in Patients With Autoimmune Hepatitis: An International Multicenter Study. Issue 6 (18th June 2021) - Efe, Cumali; Dhanasekaran, Renumathy; Lammert, Craig; Ebik, Berat; Higuera‐de la Tijera, Fatima; Aloman, Costica; Rıza Calışkan, Ali; Peralta, Mirta; Gerussi, Alessio; Massoumi, Hatef; Catana, Andreea M.; Torgutalp, Murat; et al.
Abstract : Background and Aims: Data regarding outcome of COVID‐19 in patients with autoimmune hepatitis (AIH) are lacking. Approach and Results: We performed a retrospective study on patients with AIH and COVID‐19 from 34 centers in Europe and the Americas. We analyzed factors associated with severe COVID‐19 outcomes, defined as the need for mechanical ventilation, intensive care admission, and/or death. The outcomes of patients with AIH were compared to a propensity score–matched cohort of patients without AIH but with chronic liver diseases (CLD) and COVID‐19. The frequency and clinical significance of new‐onset liver injury (alanine aminotransferase > 2 × the upper limit of normal) during COVID‐19 was also evaluated. We included 110 patients with AIH (80% female) with a median age of 49 (range, 18‐85) years at COVID‐19 diagnosis. New‐onset liver injury was observed in 37.1% (33/89) of the patients. Use of antivirals was associated with liver injury ( P = 0.041; OR, 3.36; 95% CI, 1.05‐10.78), while continued immunosuppression during COVID‐19 was associated with a lower rate of liver injury ( P = 0.009; OR, 0.26; 95% CI, 0.09‐0.71). The rates of severe COVID‐19 (15.5% versus 20.2%, P = 0.231) and all‐cause mortality (10% versus 11.5%, P = 0.852) were not different between AIH and non‐AIH CLD. Cirrhosis was an independent predictor of severe COVID‐19 in patients with AIH ( P < 0.001; OR, 17.46; 95% CI, 4.22‐72.13). Continuation of immunosuppression or presence of liver injury during COVID‐19 was not associated with severe COVID‐19. Conclusions: This international, multicenter study reveals that patients with AIH were not at risk for worse outcomes with COVID‐19 than other causes of CLD. Cirrhosis was the strongest predictor for severe COVID‐19 in patients with AIH. Maintenance of immunosuppression during COVID‐19 was not associated with increased risk for severe COVID‐19 but did lower the risk for new‐onset liver injury during COVID‐19.